ENVIRONMENTAL QUALITY IN EUCALYPTUS SPP. PLANTATIONS DETERMINED FROM FUNCTIONAL PROCESSES OF ITS LITTER - Pinto, Winkler José; Negreiros, André Batista de (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
The objective of the study was to understand the influence of Eucalyptus spp. cultivation on the quality of the environment in which it is inserted. For this, three sampling areas of eucalyptus plantations and a control area composed of heterogeneous vegetation. Measurements of leaf litter mass loss, water retention capacity (WRC) tests, and measurements of the content of macronutrients and organic fractions (lignin, cellulose and polyphenols) were carried out in the litter. The litter samples from the control area showed a decomposition coefficient (k) (0.78; 0.82; 0.87) significantly higher than the samples from Eucalyptus spp. (0.51; 0.52; 0.55). For WRC, samples from the control area showed values between 161% and 339%, with an average value of 260%. These were significantly higher than those in the eucalyptus areas, which varied between 72% and 156%, with an average value equal to 112%. As for the content of macronutrients, for the concentration of N, Mg and S in the litter, the samples collected in the control area showed average values significantly higher than the samples from the eucalyptus areas. Regarding the contents of lignin and polyphenols, the samples collected in the eucalyptus areas showed significantly higher values than those presented by the control area. The results obtained showed a strong statistical correlation between the contents of N, Mg, lignin and polyphenols in the sampled leaf material, decomposition rates and water retention capacity. The decomposition of Eucalyptus spp. presented slow decomposition, strongly linked to its chemical composition, which hinders the action of decomposing agents.